PENGARUH PENAMBAHAN KATEKIN DAUN TEH HIJAU (Camellia sinensis) 10% PADA PERIODONTAL DRESSING TERHADAP PROLIFERASI HUMAN PRIMARY FIBROBLAST - , SITI RAMADANIA WIDAYATI, drg. Kwartarini Murdiastuti, Sp.Perio.(K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Periodontal dressing was developed with some additives which aimed to increase its value from a mechanical wound barrier to a wound healing agent. Fibroblast proliferation as one of the wound healing indicator need to be assessed further. One of the natural compound with wound healing potential was green tea catechins but recent studies about catechins effects regarding fibroblast proliferation had variety of results, wether enhanced or suppressed fibroblast proliferation. This study aimed to attain the effect of 10% green tea catechins addition in periodontal dressing on human primary fibroblast proliferation. This study used 3 types of periodontal dressing: Baerâs periodontal dressing (PD), Baerâs periodontal dressing with 10% green tea catechins addition (PDC), and Coe-PakTM (CP). Each periodontal dressing was immersed in natural saliva for one day then added to human primary fibroblast culture in the microplate and incubated for 24 and 72 hours. After the incubation period, proliferation test conducted with MTT assay which resulted optical density (OD) value. Data then analyzed by MANOVA, LSD, and Independent T Test. Statistical analysis of OD value after 24 hours incubation showed that there were no significant differences (p>0,05) among CP, PD, and PDC whereas data of 72 hours incubation showed significant differences (p<0,05). OD value of PDC was lower than CP and PD while there was no significant difference (p>0,05) between CP and PD. In conclusion, 10% green tea catechins addition in periodontal dressing inhibited human primary fibroblast proliferation. Keywords: Green tea catechins, periodontal dressing, proliferation, human primary fibroblast